Ответ:
15
Пошаговое объяснение:
Пусть числа эти a b c
1) a+0.1a
b+0.2b
c
c+(a+0.1a) +(b+0.2b)=a+b+c+1
2) a
b+0.1b
c-0.1c
a+(b+0.1b)+(c-0.1c)=a+b+c-0.5
3) a+0.2a
b
c+0.4c
(a+0.2a)+b+(c+0.4c)=a+b+c+4
Cложим условия 1), 2), 3)
(a+b+с)+(a+0.1a) +(b+0.2b)+(b+0.1b)+(c-0.1c)+(a+0.2a)+(c+0.4c)=3(a+b+c)+4.5
(a+0.1a) +(b+0.2b)+(b+0.1b)+(c-0.1c)+(a+0.2a)+(c+0.4c)=2(a+b+c)+4.5
2a+0.3a+2b+0.3b+2c+0.3c=2(a+b+c)+4.5
2(a+b+c)+0.3(a+b+c)=2(a+b+c)+4.5
0.3(a+b+c)=4.5
a+b+c=15
Подробнее - на Znanija.com - znanija.com/task/33123300#readmore